2008
DOI: 10.1080/10826080801922744
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Substance Use Among South African Primary Care Clinic Patients

Abstract: We aimed to assess prevalence and correlates of hazardous use of tobacco, alcohol and other drugs in a primary care population in Cape Town, South Africa. Stratified random sampling was used to select 14 of the 49 clinics in the public health sector in Cape Town, and every "nth" patient, with those ages 18-25 oversampled (N = 2,618). Data were collected from December 2003 through 2004, using the World Health Organization Alcohol, Smoking, and Substance Involvement Screening Test. Hazardous use of tobacco was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
28
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 32 publications
10
28
1
Order By: Relevance
“…A South African study conducted in primary care clinic showed an AUDs prevalence of 17.6 % [37]. A population based study conducted in Thailand and Singapore the prevalence of AUDs was 10.9% and 3.6% respectively [34,35].…”
Section: Discussion Prevalence Of Alcohol Use Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…A South African study conducted in primary care clinic showed an AUDs prevalence of 17.6 % [37]. A population based study conducted in Thailand and Singapore the prevalence of AUDs was 10.9% and 3.6% respectively [34,35].…”
Section: Discussion Prevalence Of Alcohol Use Disordersmentioning
confidence: 99%
“…Between 76% and 85% of people in low and middle-income countries with severe mental disorders receive no treatment for their mental health conditions as well as for their comorbid substance abuse in general. Secondary prevention in earlier stages of drinking problems is virtually nonexistent in these countries [31][32][33][34][35][36][37][38][39][40][41]. There is a shortage of information related to AUDs and its associated factors among psychiatric outpatients.…”
Section: Introductionmentioning
confidence: 99%
“…Lower socioeconomic status, no school education in women, and being older than 25 years of age were associated with alcohol problems. Peltzer (2006) found that male gender and being single, divorced, or widowed predicted harmful drinking, and Ward et al (2008) found that male gender, younger age (men), no religious involvement, employment, some high school education (compared with less [e.g., no high school] or more [e.g., completing high school] education), and higher stress were associated with hazardous alcohol use. The apparent contradiction in socio-economic status and employment fi ndings may be because, in a low-to middle-income country such as South Africa, the poorest segments of society may be unable to purchase alcohol.…”
Section: T He South African Demographic and Healthmentioning
confidence: 99%
“…This can be compared with findings from a study on correlates of substance use among patients which also found that more males than females used substances (Ward C. et al, 2008). Men are more likely to report alcohol use, to drink alcohol more frequently, and to be identified as harmful, hazardous, or likely dependent drinkers than women (Kalichman S. et al, 2007).…”
Section: Discussion:-mentioning
confidence: 99%